The competition effect of strain and interatomic distance on ferromagnetic critical temperature in ising ultra-thin-film: Monte carlo simulation - Yongyut Laosiritaworn (2018)
This work used Monte Carlo simulation to investigate the effect of lattice strain on critical temperature of the ferromagnetic Ising ultra-thin-film. Using Bethe-Slater interpretation, exchange interaction was assumed Lennard-Jones (LJ) potential function, and becomes functions of interatomic distance. The cluster flip algorithm was used to update the spin configuration, where energy and magnetization were measure to extract critical temperature via the fourth order cumulant of the magnetization. Results show that initial interatomic distance and strain have strong effect on magnetic critical point behavior. The critical point can be enhanced or suppressed depending on how exchange interaction is modified by the values of initial interatomic distance and strain. A scaling function in predicting critical temperatures is also given in this work. Results agree well with previous applicable works, which confirms the reliability of the reported results. © (2013) Trans Tech Publications, Switzerland.